To find composition of two functions f and g, we have to follow the procedure given below.
Step 1 :
In (f∘g) (x),
Write f and remove the composition sign. Inside the bracket put the function g(x). So, we will get
(f∘g) (x) = f[g(x)]
Step 2 :
In the place of g(x), put the respective function.
Step 3 :
Now the function g(x) is like a input for the function f(x). So, apply the function g(x) in the place of x in the function f(x).
Example 1 :
If f(x) = 3x - 5 and g(x) = x2, find (f∘g) (x).
Solution :
(f∘g) (x) = f ( g(x) )
Here the value of g(x) is x2.
(f∘g) (x) = f ( x2 )
f (x2) looks like f(x), here x = x2
So, in the function f(x) put x2, where we see x.
(f∘g) (x) = 3x2 - 5
Example 2 :
Let f(x) = -3x + 7 and g(x) = 2x2 - 8, find (f∘g) (x) and (g∘f) (x).
Solution :
(i) f(x) = -3x + 7 and g(x) = 2x2 - 8
(f∘g) (x) = f (g(x) )
= f(2x2 - 8)
Now in f(x), x can be replaced by 2x2 - 8.
f(2x2 - 8) = -3(2x2 - 8) + 7
Distributing -3 and combining like terms, we get
= -6x2 + 24 + 7
= -6x2 + 31
(ii) (g∘f) (x) = g( f(x) )
= g(-3x + 7)
Now in g(x), x can be replaced by -3x + 7
g(-3x + 7) = 2(-3x + 7)2 - 8
Using the algebraic identity, expanding it.
g(-3x + 7) = 2(9x2 - 42x + 49) - 8
= 18x2 - 84x + 98 - 8
= 18x2 - 84x + 90
Example 3 :
If f(x) = -9x - 9 and g(x) = √(x - 9), find (f∘g) (x).
Solution :
(f∘g) (x) = f( g(x) )
= f( g(x) )
Example 4 :
If f(x) = -2x + 1 and g(x) = √(x2 - 9), find
(i) (f∘g) (x) and
(ii) (g∘f) (x)
Solution :
Finding (f∘g) (x) :
Finding (g∘f) (x) :
Example 5 :
If f(x) = -2x + 1 and g(x) = √(x2 - 5), find
(i) (f∘g) (x) and
(ii) (g∘f) (x)
Solution :
(i) Finding (f∘g) (x) :
(f∘g) (x) = f ( g(x) )
Here the value of g(x) is √(x2 - 5).
= f(√(x2 - 5))
In the function f(x), we will apply x as √(x2 - 5).
f(g(x)) = -2(x2 - 5) + 1
= -2x2 + 10 + 1
= -2x2 + 11
(ii) Finding (g∘f) (x) :
(g∘f) (x) = g ( f(x) )
Here the value of f(x) is -2x + 1.
g ( f(x) ) = g(-2x + 1)
Here g(-2x + 1) exactly matches with g(x). So, apply x as -2x + 1 in the function g(x).
= √((-2x + 1)2 - 5)
= √(4x2 - 4x + 1 - 5)
= √(4x2 - 4x - 4)
= √4(x2 - x - 1)
= 2√(x2 - x - 1)
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM